A Technique of Time Synchronization in Pseudolite System Based on Single-difference Method. Issue 1 (January 2021) - Liu, Haiqing; Zhao, Li; Huang, Xing; Tang, Qiaoxiao
Abstract: Aiming at the time synchronization problem of pure pseudolite system in high precision positioning, a technique of time synchronization in pseudolite system based on single-difference method is proposed. The reference receiver with dual-antenna and the carrier phase observation equation are used and phase integer ambiguity is adjust-ed by the least-squares ambiguity decorrelation adjustment (LAMBDA) method. High precision synchronization of the system clock can be realized through the clock error broadcast or centralized processing. Both theoretical derivation and simulation show that the system is able to provide high accuracy time synchronization and the precision of synchronization can reach 0.02 ns.